PENINGKATAN HASIL BELAJAR MENGGUNAKAN METODE BERMAIN PERAN DI KELAS V SEKOLAH DASAR - DEWI, YUREFNI (Universitas Negeri Padang, 2014)
The purpose of this research is to describe the improvement of students’ achievements used Role Play Method at Grade V SDN 06 Ladang Padi Surian. The subject of this research were teacher and 22 grade V students.The result of lesson plan observation on cycle I was 69.64%, and cycle II was 89.28%. The observation of teacher on cycle I was 73.86%, and cycle II was 86.36%. The observation of students on cycle I was 75.00%, and cycle II was 84.09%. The resut of students’ achievement cycle I was 69.58, and cycle II was 85.35. Therefore, Role Play could improve the students’ achievement at Grade V.Kata Kunci: Hasi Belajar, Metode Bermain Peran